Factors affecting individual customers' access to financial inclusion through the frequency of using services of commercial banks in An Giang province - Vu, Cẩm Nhung; Luu, Phước Vẹn (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
This study aims to determine and measure the impact of factors affecting financial inclusion of individual customers through the frequency of using services of commercial banks in An Giang province. The study was conducted by interviewing individual customers who used the services of commercial banks in An Giang province. As a result, 169 surveys were satisfactory and were cleaned, coded and processed using SPSS 20.0 software. The built regression equation is suitable, there are 3 independent variables in the research model that have a positive impact on the frequency of using banking services as follows: the purpose of opening a bank account, the convenience and accessibility of bank branch. On the basis of the findings, the authors also makes conclusions and recommendations to help financial institutions develop banking products and services, improve the ability of individual customers to access comprehensive finance through the service of Vietnamese commercial banks so that people can access and use useful financial products and services at reasonable costs to meet their needs, contribute to poverty alleviation, economic development. sustainable economy.